1967
DOI: 10.1002/pol.1967.150050115
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of thietane

Abstract: SPnoPeisGrignard reagentrinitiated polymerization of thietane gave a soluble crystalline polymer melting at 59°C. Oxidation of the polymer with one or two equivalents of hydrogen peroxide gave the sulfoxide and sulfone, respectively. The sulfoxide was noncrystalline and insoluble in all common solvents at mom temperature and softened at 185-200°C. The sulfone was partially orystalline and insoluble. * This polymer (MW 2000, m.p. 5657°C. has been reported earlier from the reaction of sodium with bis(ychloroprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Contrarily, the anionic ring‐opening polymerization of four‐membered rings of cyclic sulfides, that is, thietanes, ( Scheme ) is far more limited . Nevertheless, thietane and its derivatives were successfully polymerized to high molar mass polymers only by initiation with Grignard reagents, such as butyl lithium .…”
Section: Chemistrymentioning
confidence: 99%
“…Contrarily, the anionic ring‐opening polymerization of four‐membered rings of cyclic sulfides, that is, thietanes, ( Scheme ) is far more limited . Nevertheless, thietane and its derivatives were successfully polymerized to high molar mass polymers only by initiation with Grignard reagents, such as butyl lithium .…”
Section: Chemistrymentioning
confidence: 99%
“…Ether‐containing four‐membered rings (oxetanes) are generally supposed to be more prone than three‐membered ones (epoxides) to undergo ring opening through a cationic mechanism, mostly due to their higher basicity (ring strain and steric hindrance being substantially similar) 73. However, their well‐known cationic ring‐opening polymerisation74 fails when applied to thietanes,75 providing highly branched/cross‐linked materials: the active four‐membered sulfonium ions undergo not only propagation, due to the attack by monomers, but also termination due to the attack by thioethers of the polymer chains formed, which produce non‐cyclic and, therefore, unreactive sulfonium ions and short branches in the main chain (Scheme ). Therefore, other than in a few isolated cases, such as the production of core cross‐linked core‐shell block‐copolymeric structures,76 or the polymerisation of 3‐chorothietane77 (where the electron‐withdrawing effect of chlorine may reduce the nucleophilicity of the main chain sulfur atoms), this mechanism has seldom been used.…”
Section: Preparative Strategies For Polysulfidesmentioning
confidence: 99%
“…Although oxetanes can undergo anionic ring‐opening polymerisation, this takes place most commonly after the activation of the ring through complexation with Lewis acids 78. On the other hand, early polymerisation experiments had demonstrated that polymers can be obtained from thietanes utilising simple nucleophiles, such as Grignard reagents, as initiators 75. Further studies on the anionic polymerisation of thietanes have highlighted a peculiar behaviour: unless very polar solvents and high monomer concentrations are used, thiolates79 or delocalised anions (such as sodium naphthalene,79 styryl lithium70) are incapable of or ineffective in initiating this polymerisation.…”
Section: Preparative Strategies For Polysulfidesmentioning
confidence: 99%
See 1 more Smart Citation
“…1,3,4 Oxidative metamorphosis of polymer backbone has not been much studied except for reports on the oxidation of some polymonosulfides. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] We wish to examine here successive oxidative metamorphosis of a disulfide polymer backbone to its respective mono-, di-, tri-and tetraoxide counterparts. Such backbone modifications on sulfide polymers is of considerable technological importance because the resultant oxidized polymers may find wide applications as oxidizing agents, compatibilizers, polymeric solvents, insulating materials, biocompatible membranes, etc.…”
Section: Introductionmentioning
confidence: 99%